2014
DOI: 10.3109/09637486.2014.898259
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional recovery withokaradiet prevented hypercholesterolemia, hepatic steatosis and glucose intolerance

Abstract: We assessed the biological value of an okara diet and its effects on the hormonal and metabolic profile of rats submitted to protein restriction during intra-uterine life and lactation and recovered after weaning. Male rats from mothers fed either 17% or 6% protein during pregnancy and lactation were maintained on 17% casein (CC, LC), 17% okara (CO, LO) or 6% casein (LL) diets over 60 d. The nutritional quality of the okara protein was similar to that of casein. The okara diet was effective in the nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
1
2
Order By: Relevance
“…While several other okara studies reported anthropometric improvements, hypolipidemia, and improved glucose tolerance with okara consumption, [ 23,24 ] we observed no such changes possibly because the content of okara in our study is lower than the previous studies. These cardiometabolic and anthropometric improvements are attributed to the physicochemical properties of dietary fiber even at intervention dosages less than 15 g day −1 but may require a longer intervention duration for a more pronounced effect.…”
Section: Discussioncontrasting
confidence: 99%
“…While several other okara studies reported anthropometric improvements, hypolipidemia, and improved glucose tolerance with okara consumption, [ 23,24 ] we observed no such changes possibly because the content of okara in our study is lower than the previous studies. These cardiometabolic and anthropometric improvements are attributed to the physicochemical properties of dietary fiber even at intervention dosages less than 15 g day −1 but may require a longer intervention duration for a more pronounced effect.…”
Section: Discussioncontrasting
confidence: 99%
“…A similar triglyceride-lowering action was observed in mice fed the 20.5% okara fiber diet, but not in those fed the 13% okara fiber diet (18). In contrast, Lemes et al did not observe hypotriglyceridemic action of the okara diet containing ~16% dietary fiber in rats irrespective of its hypocholesterolemic action (34). The discrepancy in hypotriglyceridemic action between our and their studies may be partly due to difference in animal species and diets (a low-fat diet in Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…These factors culminate in systemic inflammation and its linked complications, including impaired glucose metabolism and insulin resistance. 15 Assessing the effect of the okara soy diet on mice's hormonal and metabolic profile on a proteinrestricted diet during intrauterine life and lactation.…”
Section: Resultsmentioning
confidence: 99%
“…A study showed that it was effective in restoring nutrition in malnourished rats in early life. 15 The administration of soy to the group of recovering rat offspring showed a higher weight gain than that of those fed with a low protein diet. Meanwhile, at the end of the recuperation phase, the rats' body weights and total energy intake from this group remained lower than those of the rats in the control group.…”
Section: Plant Protein As An Alternative Source Of Proteinmentioning
confidence: 97%